Allo‐anti‐M: Detection peaks around 2 years of age, but may be attenuated by red blood cell transfusion. Issue 9 (21st July 2021) - Tamai, Yoshiko; Ohto, Hitoshi; Yasuda, Hiroyasu; Takeshita, Akihiro; Fujii, Nobuharu; Ogo, Hiroaki; Yazawa, Yurika; Hato, Takaaki; Mitani, Kinuko; Suzuki, Keijiro; Yokohama, Akihiko; Kato, Yoko; et al.
Abstract: Background: Anti‐M is frequently observed as a naturally occurring antibody of little clinical significance. Naturally occurring anti‐M is often found in children although the specific triggers of production, persistence, and evanescence of anti‐M have yet to be elucidated. Methods: In a retrospective, multicenter, nationwide cohort survey conducted from 2001 to 2015, alloantibody screening was performed before and after transfusion in 18, 944 recipients younger than 20 years. Recipients were categorized into six cohorts based on their age at transfusion; within and among these cohorts, allo‐anti‐M was analyzed in regard to its production, persistence, and evanescence. Results: In 44 patients, anti‐M detected before and/or after transfusion was an age‐related phenomenon, with a median age of 2 years and an interquartile range of 1–3 years; anti‐M was most frequently detected in a cohort of children 1 to <5 years (0.77%, 31 of 4035). At least five patients were presumed to have concurrent infections. Among 1575 adolescents/young adults (15 to <20 years), no anti‐M was detected. Of 29 patients with anti‐M prior to transfusion, the antibody fell to undetectable levels in 17 recipients (89.5%, of whom at least 13 received only M‐negative red cells) after anywhere from 5 days to 5.8 years; anti‐M persisted in 2, and was not tested in 10. Only 15 recipients (0.08%) produced new anti‐M after transfusion. Conclusion: Naturally occurring anti‐M is a phenomenon of younger ages, predominantly between 1 and 3 years. After transfusion, it often falls to undetectable levels.